Structural and mechanical properties of Cr-Zr-N coatings with different Zr content - Aissani, Linda; Fellah, Mamoun; Nouveau, Corinne; Abdul Samad, Mohammed; Montagne, Alex; Iost, Alain (Surface engineering, 2020)
Cr-Zr-N films have been synthesised using R.F reactive magnetron sputtering system on Si (100) wafer and XC100 steel substrate without heating. The structural, mechanical and friction coefficient evolution as a function of the Zr content were investigated by XRD, (EDS, WDS), WPS, XPS, SEM, AFM, nanoindentation, Scratch adhesion and pin-on-disc sliding wear tests. The results show, that, with increasing Zr content, the film structure changed with the coexistence of (Cr-N, Zr-N) crystallographic orientation mixture. The films formed a (Cr, Zr) N solid solution where Zr atoms substitute Cr atoms. CrN lattice parameter increased from 4.17 to 4.32 Å with the crystallite size refinement. The mechanical parameters (H, σ, E, H/E and H 3 /E 2 ) were significantly improved in comparison to binary films, especially at 29 at.-% Zr. The friction and wear behaviour of the Cr-Zr (29 at.-% Zr)-N coating also showed a significant improvement.